Study on Physico-chemical Quality of Beef In The Market of Malang City - Heru Prasetyo; Masdiana Ch Padaga; Manik Eirry Sawitri (Faculty of Animal Science Universitas Brawijaya, 2013)
Results of this research indicate that the physical qualities of the beef include the average value of pH 5.6 for Dinoyo market; Blimbing market was 5.7; Besar market was 5.6. Average WHC values of Dinoyo market was 36.13%; 30.79% for Blimbing market, and 29.67% for Besar market. Average texture value of Dinoyo market was 10.56%, 12.82% for Blimbing market; and 12.89% for Besar market. As for the chemical quality include the value of the average moisture content of 77.65% for Dinoyo market; 76.05% for Blimbing market, and 76.03% for Besar market. Value of the average fat content was 14.7% for Dinoyo market; 14.34% for Blimbing market, and 15.43% for Besar market. The value of an average protein content was 18.26% for Dinoyo market; 18.1% for Blimbing market, and 19.19% for Besar market.Â Key words: beef, pH, WHC, texture, water, fat, protein